OFR-92-77 Personal Samplers For CO, NO And NO2 In Air - E. D. Palmes (The National Institute for Occupational Safety and Health (NIOSH), 1977)
This report was prepared by New York University Medical Center, Institute of Environmental Medicine, 550 First Avenue, New York, New York under USBM Grant Number G0133066, Personal Samplers for CO, NO and NO2 in Air. The grant was initiated under the Coal Mine Health and Safety Program. It was administered under the technical direction of the Pittsburgh Mining and Safety Research Center with Dr. George H. Schnakenberg acting as the Technical Project Officer. Mr. L. Young was the contract administrator for the Bureau of Mines. This report is a summary of the work recently completed as part of this grant during the period 3/1/73 to 11/30/76. This report was submitted by the authors in March, 1977.